Culture-based breast milk and infant gut microbiota profiles among stunted infants: A case-control study from Indonesia - Aslinar Aslinar; Herlina Dimiati; Nur Indrawati; Sofia Sofia (Narra Sains Indonesia, 2026)
Stunting remains a major public health problem in Indonesia. Early-life microbiota may contribute to infant growth through their roles in microbial colonization, immune maturation, intestinal function, and nutrient utilization, but evidence from high-stunting settings in Indonesia remains limited. The aim of this study was to compare culture-based breast milk and infant fecal microbiota profiles between stunted and normal infants in Aceh, Indonesia, and to examine their associations with maternal, postnatal, environmental, and socioeconomic factors. A total of 54 breastfed infants aged 6–11 months were included, consisting of 27 stunted and 27 normal infants matched by age and sex. Breast milk and fecal samples were analyzed using culture-based microbiological methods for bacterial identification and colony-forming unit counts. In breast milk, Streptococcus sp. and Staphylococcus sp. were the predominant bacteria, with higher detection frequencies among mothers of stunted infants. In fecal samples, Escherichia coli was the most frequently detected bacterium in both groups, while Staphylococcus aureus and Clostridium innocuum were significantly more common among stunted infants. Breast milk bacterial colony counts were significantly higher in the stunted group, whereas fecal colony counts were numerically higher but not statistically significant. Poor household sanitation was more frequent among stunted infants. Exploratory analyses among stunted infants showed that maternal height was associated with Anaerococcus prevotii, while maternal education was associated with selected fecal bacteria, including Salmonella choleraesuis, Proteus mirabilis, and Eggerthella lenta. These findings suggest culture-detectable differences in breast milk and infant fecal microbiota between stunted and normal infants. Given the small sample size, confirmation using longitudinal and sequencing-based studies is warranted.